The spatial spillover effect of ICT development level on regional CO2 emissions - Jinqi Su; Wenbo Wang; Shiyao Tang (Scientific Reports, 2023)
Abstract Information and communication technology plays an essential role in affecting CO2 emissions and promoting green and sustainable development. This paper empirically examines the effect of the level of urban ICT development on CO2 emissions using panel data for Chinese cities from 2010 to 2020. On this basis, a spatial Durbin model is used to analyze the spatial spillover effects of ICT development level affecting regional CO2 emissions, and its direct, indirect and overall effects are further analyzed. The conclusions of the study are as follows. (1) The CO2 emissions of Chinese cities are correlated by spatial distance and show high-high or low-low clustering characteristics. (2) ICT development can reduce CO2 emissions in the region and increase CO2 emissions in neighboring regions. This conclusion still holds after several robustness tests. And when the level of ICT development increases by 1 standard deviation, CO2 emissions are reduced by 64%. (3) The mechanism of action shows that ICT can influence regional CO2 emissions through its technological innovation effect and industrial upgrading effect. (4) The impact of ICT development on regional carbon emissions is characterized by significant heterogeneity depending on the city's geographical location and whether or not environmental information is publicly available.